(untitled) - bruce Hallberg (Indiana, 1996)
Introducing Microsoft Exchange server; Planning your Microsoft Exchange server system; Installation; Administering exchange server; Using Microsoft exchange server; Application development with MES.
Keywords: microsoft exchange,client/server computing